PS01.025: CONSEQUENCES OF MUCOSAL PERFORATION FROM LAPAROSCOPIC HELLER MYOTOMY: A SYSTEMATIC REVIEW. (14th September 2018) - Maurice, Andrew; Malik, Hassan; Pearson, Thomas; Dodd, Benjamin
Abstract: Background: Mucosal perforation is a common complication of Laparoscopic Heller Myotomy (LHM) for achalasia. Perforations discovered intra-operatively are usually treated with laparoscopic suturing. Perforations not identified at the time of operation generally present with sepsis and a leak. We aimed to document every reported case of mucosal perforation in the literature following this procedure and define the prognostic significance of this complication. Methods: A systematic literature search was performed using the PubMed database with the key-phrases 'achalasia' and 'laparoscopy' or 'laparoscopic'. All English-language case series and trials were included that reported at least one mucosal perforation from 1997 to 2017. Two researchers appraised the literature for inclusion. For centers with multiple publications, the largest series was chosen for inclusion. Results: Of 901 articles retrieved, 100 studies were included after duplicates were excluded. 672 mucosal perforations were reported in 8705 LHM procedures (7.7%, range 0.5–30%). 635 perforations were identified intra-operatively. 609 (96%) were repaired with laparoscopic suturing with or without fundoplication and no clinical sequelae. 22 (3.5%) were converted to open procedures. No deaths or long-term morbidity was reported in procedures where perforations were identified intra-operatively. There were 37 definitive missed mucosal perforations that were identified post-operatively. 3 patients died. For those that survived, 22 returned to theatre, 2 were treated with radiological drainage and 10 were managed conservatively with long-term antibiotics. Due to differences in reporting nomenclature and definitions, the actual rate of missed mucosal perforations may be higher. Conclusion: Mucosal perforation during LHM is rarely of prognostic significance if it is repaired with laparoscopic suturing at the time. Mucosal perforations identified post-operatively can result in re-operation, sepsis, prolonged hospital stay and death. Care should be taken to ensure any mucosal perforation is detected and repaired intra-operatively. Disclosure: All authors have declared no conflicts of interest.